Combined modified atmosphere packaging and guar gum edible coatings to preserve blackberry (Rubus glaucus Benth) - Pérez, Diego A (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2021)
Blackberry fruits are fresh products with wide market possibilities but of very limited shelf life (3-6 days). To develop preservation alternatives, the effect and interaction of a modified atmosphere packaging and an edible coating based on guar gum were determined on the shelf life and quality properties of blackberry cv. Castilla stored at 5 ℃. Three types of packaging were evaluated: (1) perforated polyethylene terephthalate clamshells, (2) sealed polyethylene terephthalate clamshells, and (3) sealed polyethylene terephthalate clamshells with a polylactic acid film on top. In turn, two types of coating were evaluated: coatings of guar gum solutions at (1) 0.3% and (2) 0.4% in water. During storage, an index of deterioration and different quality properties were evaluated. In the polyethylene terephthalate packages with polylactic acid, an equilibrium modified atmosphere packaging was formed. Weight loss was much lower for the sealed polyethylene terephthalate and polyethylene terephthalate + polylactic acid (<2%) compared to fruits in perforated clamshells, with no significant differences between these two types of packaging. It was possible to observe the treatment with an edible coating of 0.3% gum guar and perforated clamshells (guar gum 0.3/N) presented the lowest deterioration rate and preserve the fruit longer time (13 days) although with a high weight loss (23.23%) while the treatment with polyethylene terephthalate and polylactic acid film + edible coating of gum guar (guar gum 03/polylactic acid) kept the samples during 12 days with a lower weight loss (1.75%). This latter combination of equilibrium modified atmosphere packaging with a biodegradable film and the guar gum edible coating can be an interesting treatment from a commercial point of view